Again on 1968: some remarks on recent Italian historiography - Tolomelli, Marica (Italia Contemporanea - Sezione Open Access, 2021)
Although Italian — as well as international — historiography engaged with the fiftieth anniversary of 1968 in a very lively way, it was probably not groundbreaking in terms of its originality. From an editorial perspective, this liveliness has translated into the publication of a considerable amount of studies, which this article is able to examine only partially, given the variety of their approaches, analytical levels and interpretations. The article addresses a selection of these texts in order to discuss some of the most significant directions of research that emerge from them, in terms of methodological approaches, interpretations and arguments. These books are, in alphabetical order: Michele Battini, Un sessantotto, Università Bocconi Editore, Milano 2018; Guido Crainz (ed.), Il Sessantotto sequestrato. Cecoslovacchia, Polonia, Jugoslavia e dintorni, Donzelli, Roma 2018; Marcello Flores, Giovanni Gozzini, 1968. Un anno spartiacque, il Mulino, Bologna 2018; Monica Galfré, La scuola è il nostro Vietnam. Il ’68 e l’istruzione secondaria italiana, Viella, Roma 2019; Paolo Pombeni, Che cosa resta del ’68, il Mulino, Bologna 2018; Francesca Socrate, Sessantotto. Due generazioni, Laterza, Roma-Bari 2018.